EZMATH: DEVELOPING DIGITAL METHODS, A WEBSITE-BASED APPROACH TO SUPPORT TEACHING MATH WITH FIRST-GRADE VIETNAMESE CHILDREN WITH DYSCALCULIA - Thi Quynh Hoa, Nguyen; Thi Cam Huong, Nguyen; Thanh Ha, Le; Thi Duyen, Ngo (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Dyscalculia is a term used to describe specific learning disabilities related to understanding numbers that affect the ability of children of all ages to understand, learn, and perform mathematics and number-based calculations. Estimates of the prevalence of dyscalculia range from 3% to 6% of the population, indicating the need for timely support solutions for teaching mathematics to students with mathematical difficulties. Therefore, the general objective of this study is to develop a digital tool in the form of an interactive learning website that provides many features and flexibility for children with dyscalculia. The solution was surveyed with 73 people working in and researching education for children with dyscalculia. The results show that the proposed solution is initially assessed to be appropriate and to offer an opportunity for developing a potential learning method to support children with dyscalculia.